Enhancement in Hardness and Influence of Artificial Aging on Stir Cast Al6061-B4C and Al6061-SiC Composites. (2018) - Gowri Shankar, M.C.; Shettar, Manjunath; Sharma, S.S.; Kini, Achutha; Jayashree
Abstract: Present investigation focusses on individual effect of B4 C and SiC on the improvement in hardness with an average size of 35-40μm and various weight percentage of (2, 4 and 6) Al6061 alloy composite. Composites are produced by stir casting process. The precipitation hardening effect at 100, 150 and 200°C on the mechanical properties was also investigated. Optical micrographs and Brinel hardness number have been discussed. Transmission electron microscope shows precipitation of finer inter-metallic in both Al6061 alloy and its composites. Increase in percentage of both B4 C and SiC reinforcement from 2-6% wt. and artificially aged at 100°C shows enhancement in hardness by 150-175% due to the precipitation of intermetallic phases of alloying elements. Al6061-B4 C composites show improvement in hardness as compared to Al6061-SiC composites.